2003
DOI: 10.1038/nm864
|View full text |Cite
|
Sign up to set email alerts
|

Activation and regulation of Toll-like receptors 2 and 1 in human leprosy

Abstract: The expression and activation of Toll-like receptors (TLRs) was investigated in leprosy, a spectral disease in which clinical manifestations correlate with the type of immune response mounted toward Mycobacterium leprae. TLR2-TLR1 heterodimers mediated cell activation by killed M. leprae, indicating the presence of triacylated lipoproteins. A genome-wide scan of M. leprae detected 31 putative lipoproteins. Synthetic lipopeptides representing the 19-kD and 33-kD lipoproteins activated both monocytes and dendrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
249
1
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(267 citation statements)
references
References 45 publications
5
249
1
12
Order By: Relevance
“…Importantly, and confirming the in vivo relevance of theses findings, TLR2 expression on CD14 þ cells was lower in healthy volunteers with shorter alleles than in those without them. Although the promoter activities of constructs including GT repeats and expression of TLR2 on CD14 þ cells did not upregulate with LPS or whole lysates of M. tuberculosis in this study, the decrements of TLR2 expression on human cells by various stimulation 49 or during exposure to M. tuberculosis have been reported. 50 The essential role of TLR2 against mycobacterial infection in vivo has been shown by rapid fatality 28,29 and higher burden of mycobacteria 51 in TLR2-deficient mice.…”
Section: Discussioncontrasting
confidence: 69%
“…Importantly, and confirming the in vivo relevance of theses findings, TLR2 expression on CD14 þ cells was lower in healthy volunteers with shorter alleles than in those without them. Although the promoter activities of constructs including GT repeats and expression of TLR2 on CD14 þ cells did not upregulate with LPS or whole lysates of M. tuberculosis in this study, the decrements of TLR2 expression on human cells by various stimulation 49 or during exposure to M. tuberculosis have been reported. 50 The essential role of TLR2 against mycobacterial infection in vivo has been shown by rapid fatality 28,29 and higher burden of mycobacteria 51 in TLR2-deficient mice.…”
Section: Discussioncontrasting
confidence: 69%
“…Support for this hypothesis came from the fact that previous studies have demonstrated that the phagocytosis of P. falciparum-parasitized erythrocytes is enhanced by PPARc ligands without TNF-a production [11]. In addition, it has previously been shown that Th2 cytokines like IL-4 activate PPARc in Mu [18] while this cytokine down-regulates TLR2 expression [42], suggesting that TLR2 and PPARc are opposite signaling pathways.Here, we have provided evidence that IL-13 upregulates CD36 surface expression in human monocytes and increases CD36 mRNA. Our results demonstrate for the first time that IL-13 up-regulates CD36 via PPARc.…”
mentioning
confidence: 99%
“…Mature DCs migrate from the infected/inflamed tissue and enter lymphatic circulation, presumably directed by up-regulation of surface expression of CCR7, the only chemokine receptor expressed by mature DCs (5). M. leprae activates DCs via TLR2-TLR1 heterodimers, presumably through triacylated lipoproteins like the 19-kDa lipoprotein (6). TLR2 polymorphisms have been linked to increased susceptibility to leprosy (7,8).…”
mentioning
confidence: 99%